The structure and performance of the delivery systems for tsetse and trypanosomosis control inputs and services in Kenya. - M'Mboyi, F. (University of Nairobi, 2001)
This study aims at identifying the existing institutional framework involved in the delivery of tsetse and trypanosomosis control inputs and services in Kenya with a view to determining (whether efficiency exists or not in the marketing system. The study also aims at identifying the appropriate institutional framework that enhances efficiency in the marketing system for delivery of these control inputs. The marketing structure is analysed by looking at the market share of the first four and first eight largest traders within the various channels of the tsetse and trypanosomosis control inputs marketing system. The results of analysis show that the wholesale marketing channel is the least -competitive,' followed by the pharmaceutical firms and the retail traders. According to the Bain (1968) industry classification model, there is evidence of a highly concentrated marketing system amongst the wholesale traders while the pharmaceutical firms and the retail traders have a high to moderate market concentration. The marketing structure was therefore found to be inherently imperfectly competitive and was characterized by both monopolistic and oligopolistic features. The extent of market efficiency is then analysed by looking at the market performance indicators in this market viz a viz gross margins per trading level, variable costs, opportunity cost analysis and returns to capital investments per trading level. The results of analysis show that there is evidence of inefficiency in all the studied marketing firms. The least efficient marketing channel was that controlled by the retail traders, followed by the wholesale traders. The relatively inefficient marketing channel was that controlled by the pharmaceutical firms. The results of analysis show that the retail traders had the highest returns to capital while the pharmaceutical firms had the least returns to capital. IX Although the liberalisation regime was being put in place in the livestock health sector, it vas evident that the role of the government in dealing with the tsetse problem was not adequate ls observed by the diminishing budgetary allocations to the livestock heath sector and the •educed tsetse surveillance programs necessary to monitor the tsetse belts and spread of ‘fly’ in lew pasture lands. The research therefore indicated that imperfectness and non competitiveness was nherently visible in the tsetse and trypanosomosis control inputs and services marketing system jnd that there was urgent need for a policy intervention to remedy the situation. Some of the Droposed policy recommendations included: forming of livestock farmers co-operatives to purchase tsetse control inputs at a lower per unit cost due to economies of scale; encouraging more wholesale traders to enter the wholesale channel in order to break the current cycle of their aligopolistic marketing structure; reducing information asymmetry in the market by bridging the information gap between livestock farmers and the marketing institutions. It is therefore concluded that further research has to be undertaken to ascertain the functioning of pharmaceutical firms especially in the area of pricing. This would give a clear indication of how these firms make their trading decisions and the resultant effect such an action would have in influencing the behaviour of the retail traders, the wholesale traders and the Animal Health Service Providers. More research is still needed in this area because currently, there is very little information database from which to draw inferences on the true situation in the present tsetse and trypanosomosis control inputs and services marketing system in Kenya.